Tough guy - Reid, Rachel (Reid, Rachel. Game changers series, 2024)
"Pro hockey star Ryan Price may be an enforcer, but off the ice he struggles with anxiety. Recently traded to Toronto, he's determined to make a fresh start in the city's dynamic LGBTQ+ Village. The last thing he expects to find in his new neighborhood is a blast from his past in the fabulous form of Fabian Salah. Aspiring musician Fabian loathes hockey. But that doesn't stop him from being attracted to a certain burly ginger-bearded defenseman. He hasn't forgotten the kiss they almost shared back in high school, and the chemistry between them has only intensified. Fabian is more than happy to be Ryan's guide to the gay scene in Toronto. Between dance clubs and art exhibits--and the most amazing sex--Ryan's feeling something he hasn't experienced in a long time: joy. But playing the role of the heavy on the ice has taken its toll on his body and mind, and a future with Fabian may mean hanging up his skates for good"--